Exponentially practical stability of impulsive discrete time system with delay - Sirilak Wangrat (2018)
© 2016, Wangrat and Niamsup. In this paper we investigate an impulsive discrete time system with delay. By using Lyapunov stability theory and a Razumikhin type technique, some new criteria for the exponentially practical stability of impulsive discrete time system with delay are established. A numerical example is given to show the effectiveness of our theoretical results.